Deterioration to extinction of wastewater bacteria by non-thermal atmospheric pressure air plasma as assessed by 16S rDNA-DGGE fingerprinting - El-Sayed, Wael S.; Ouf, Salama A.; Mohamed, Abdel-Aleam H. (Frontiers in Microbiology, 2015)
The impact of cold atmospheric plasma on the bacterial community structure of wastewater from two different industries was investigated by metagenomic-based PCR-DGGE utilizing 16S rRNA genes. Three doses of atmospheric pressure dielectric barrier discharge plasma were applied to wastewater samples on different time scales. DGGE revealed that the bacterial community gradually changed and overall abundance decreased to extinction upon plasma treatment. The bacterial community in food processing wastewater contained 11 key operational taxonomic units that remained almost completely unchanged when exposed to plasma irradiation at 75.5 mA for 30 or 60s. However, when exposure time was extended to 90s, only Escherichia coli, Coliforms, Aeromonas sp., Vibrio sp., and Pseudomonas putida survived. Only E. coli, Aeromonas sp., Vibrio sp. and P. putida survived treatment at 81.94 mA for 90s. Conversely, all bacterial groups were completely eliminated by treatment at 85.34 mA for either 60 or 90s. Dominant bacterial groups in leather processing wastewater also changed greatly upon exposure to plasma at 75.5 mA for 30 or 60s, with Enterobacter aerogenes, Klebsiella sp., Pseudomonas stutzeri and Acidithiobacillus ferrooxidans being sensitive to and eliminated from the community. At 90s of exposure, all groups were affected except for Pseudomonas sp. and Citrobacter freundii.